2021
DOI: 10.1002/jssc.202000834
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive chemical and metabolic profiling of anti‐hyperglycemic active fraction from Clerodendranthi Spicati Herba

Abstract: Extensive pharmacological research has demonstrated that Clerodendranthi Spicati Herba has an obvious anti-hyperglycemic effect via α-glucosidase inhibitory activity. However, the anti-hyperglycemic active fraction and its metabolic behavior in vivo have not been elaborated clearly. In this study, ultra-high-performance liquid chromatography coupled to quadrupole time of flight tandem mass spectrometry with data filtering strategy, including mass defect screening, diagnostic product ions and neutral loss ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…In a recent study, the 95% ethanol elution fraction (95% EEF) of 80% ethanol extract (0.68 g/kg, 0.34 g/kg and 0.17 g/kg) reduced blood glucose levels in an oral glucose tolerance test in normal C57BL/6J mice after 10-day administration of the extract [39]. The ethanol extract of O. stamineus (0.2 and 0.4 g/kg) obviously reduced fasting blood glucose level in high-fat-diet (HFD) C57BL/6 mice after 8-week administration of the extract [40].…”
Section: Hypoglycemic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, the 95% ethanol elution fraction (95% EEF) of 80% ethanol extract (0.68 g/kg, 0.34 g/kg and 0.17 g/kg) reduced blood glucose levels in an oral glucose tolerance test in normal C57BL/6J mice after 10-day administration of the extract [39]. The ethanol extract of O. stamineus (0.2 and 0.4 g/kg) obviously reduced fasting blood glucose level in high-fat-diet (HFD) C57BL/6 mice after 8-week administration of the extract [40].…”
Section: Hypoglycemic Activitymentioning
confidence: 99%
“…In the conformation of α-glucosidase-rosmarinic acid complex, there were 6 hydrogen bonds [66]. The 95% EEF showed higher α-glucosidase (86 µg/mL) inhibitory activity (IC50 = 40 ± 0.73 µg/mL) than acarbose (IC50 = 250 ± 1.05 µg/mL) [39]. The ethanol extract (1000 µg/mL) of some genotypes of O. stamineus inhibited α-glucosidase up to 62.84% [46].…”
Section: Inhibit the Activities Of α-Amylase And α-Glucosidasementioning
confidence: 99%
“…One animal study has shown that the water extract of O. stamineus has hypoglycemic effects on diabetic rats [ 10 ]. In a recent study, 80% ethanol extract (about 0.4 g/kg) reduced blood glucose levels in an oral glucose tolerance test in normal C57BL/6J mice and high-fat-diet (HFD) C57BL/6 mice after 1.5 [ 11 ] and 8 weeks [ 12 ] administration of the extract, respectively. Water extract of O. stamineus was also administrated orally (0.5 g/kg) to normal and diabetic rats loaded with glucose.…”
Section: Introductionmentioning
confidence: 99%
“…Many different techniques have been developed to improve the identification of in vivo metabolites of complex components of TCMs, including mass defect filter, diagnostic product ion (DPI) filter, neutral loss (NL) filter and background subtraction. Usually, these techniques were used in combination of two or three to simplify and accelerate the identification of in vivo metabolites of complex components of TCMs 15–18 …”
Section: Introductionmentioning
confidence: 99%
“…Usually, these techniques were used in combination of two or three to simplify and accelerate the identification of in vivo metabolites of complex components of TCMs. [15][16][17][18] In the study reported here, we established an enhanced strategy integrating UHPLC-QTOF-MS/MS with a data filtering strategy, including DPI and NL filters, to systematically characterize the xenobiotics in plasma, urine and feces of rat after oral administration of FCAVA. Firstly, the complex biological samples were analyzed using our reported method.…”
Section: Introductionmentioning
confidence: 99%